Perovskites : structure-property relationships - Tilley, R. J. D. (Wiley, 2016)
Uniquely describes both the crystallography and properties of perovskite related materials. -Practical applications in solar cells, micrulectronics and telecommunications -Interdisciplinary topic drawing on materials science, chemistry, physics, and geology -Contains problems and answers to enhance knowledge retention.